Tribological behaviour of an electrochemical jet machined textured Al-Si automotive cylinder liner material - Walker, J.C.; Kamps, T.J.; Lam, J.W.; Mitchell-Smith, Jonathon; Clare, Adam T. (Elsevier, 2017)
This paper investigates the use of Electrochemical Jet Machining to surface texture a hyper-eutectic Al-Si cylinder liner material. Samples were lapped to a 6μm finish followed by immersion in 1mol NaOH to expose the primary silicon colonies above the aluminium surface. Texturing was carried out using a NC system comprising of a fine gauge nozzle (cathode) jetting a solution of 2.3 mol NaCl on the surface (anode) whilst applying a current density of 220A/cm2. An array of hemispherical dimples at 1.5mm spacing was created, with an average diameter of 420μm and depth of 40μm, corresponding to an ε ratio of 0.095. Lubricated reciprocating sliding was carried out at stroke length of 25mm in a bath of PAO (4cSt) against a 52100 cylinder of 6mm diameter and 16mm length. Sliding frequencies were incremented at 1Hz intervals between 1-15Hz at 50N load increments from 50-200N. Stribeck curves indicated a reduction of the friction coefficient due to texturing of up to 0.05 in the mixed lubrication regime, representing a decrease of 38.5%. Optical profilometry and SEM indicated that abrasion and formation of a surface tribo-layer was mitigated in regions of the Al-Si surface where textured features were present parallel to the sliding direction.